Water supply - Fernando, Vijita (London, 1996)
The goals of this book are to promote understanding of water supply technologies and water supply management to enable women to make informed choices. The book also contains information on how to assess the suitability of different water supply options and how to find financial and technical assistance. This book is suitable for use by technical and non-technical project managers, project staff, extension officers, trainers and consultants concerned with women in development and women's organizations.
Keywords: Water